(untitled) (Journal of Pharma Insights and Research, 2025)
Coronary artery disease (CAD) occurs due to pathophysiological changes due to genetic predisposition and environmental factors. A systematic review of 30 studies investigating genetic polymorphisms and CAD risk revealed significant variations across global populations. The most frequently analyzed variants included angiotensin-converting enzyme (ACE) I/D, angiotensinogen (AGT) T174M/M235T, paraoxonase-1 (PON1) L55M/Q192R, and thrombospondin (TSP-1/TSP-2) polymorphisms. Case-control, cohort, and cross-sectional studies spanning populations in Europe, Asia, and North Africa demonstrated heterogeneous associations. The ACE D allele showed strong correlations with CAD risk in Romanian populations but displayed no significant associations in French cohorts. AGT variants exhibited population-specific effects on disease severity, while PON1 polymorphisms demonstrated substantial associations in Turkish and Tunisian populations. Variants in genes governing oxidative stress and vascular remodeling emerged as potential contributors to CAD pathogenesis. The heterogeneity in findings indicate the complex interaction between genetic, ethnic, and environmental determinants. Single-gene variants showed limited standalone predictive value, suggesting their optimal utility within integrated polygenic risk scores alongside traditional risk factors. A more elaborate large-scale multi-ethnic cohort studies, detailed gene-environment interaction analyses, and functional validation studies to establish causality and enable precision medicine in CAD management